ANALISIS DIFERENSIASI KONTEN MEMBACA PERMULAAN PADA PEMBELAJARAN BAHASA INDONESIA UNTUK SISWA SLOW LEARNER KELAS I SEKOLAH DASAR - Rahma, Aisyah Nayla; Hasanah, Uswatun; Satibi Hidayat, Otib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of initial reading content differentiation in Indonesian language learning for slow learners in grade I of elementary school. The method used is descriptive qualitative with data collection techniques through direct observation, in-depth interviews with class teachers, and documentation of learning tools. The results of the study indicate that content differentiation is implemented through five interrelated aspects: initial assessment based on picture letter cards during the MPLS period, simplification of content from sentences to single words with a CV-CVC pattern to reduce cognitive load, the use of picture flashcards as a visual cognitive bridge, intensive mentoring (scaffolding) strengthened by parent collaboration in the classroom, and a qualitative assessment system based on individual progress (self-referenced assessment). Although these strategies have proven to be theoretically and practically relevant, this study also identified limitations in the form of the absence of regular assessments, gradual plans to higher levels, and structured documentation of progress. This study concludes that the effectiveness of content differentiation is determined by the cohesive integration of assessments, materials, media, mentoring, and assessments that are responsive to the individual needs of slow learners.